Ultra-early weaning alters growth performance, hematology parameters, and fecal microbiota in piglets with same genetic background - Dang, De Xin; Li, Cheng Ji; Li, Shi Han; Fan, Xin Yan; Xu, Weiguo; Cui, Yan; Li, Desheng (Frontiers in Microbiology, 2022)
Piglets with the same genetic background were used to investigate the effects of different lengths of suckling period on growth performance, hematology parameters, and fecal microbiota. All piglets were born by a sow (Landrace×Yorkshire). On day 14 postpartum, a total of 16 piglets [Duroc×(Landrace×Yorkshire)] with a similar initial body weight (2.48±0.25 kg) were randomly assigned into two groups with 4 replicates per group, and two pigs per replicate pen (one barrow and one gilt). On day 14 of age, experiment started, piglets from the first group were weaned (14W) whereas the others continued to receive milk until day 28 of age (28W). Experiment completed on day 70 of age, last 56 days. Growth performance parameters including body weight, average daily gain, feed intake, feed efficiency, and growth rate, as well as hematology parameters including immunoglobulin A (IgA), immunoglobulin G (IgG), immunoglobulin M (IgM), albumin, globulin, and total protein were measured in this study. Additionally, technique of 16S rRNA Gene Sequencing was used to analyze fecal microbiota for revealing how the changes in the lengths of suckling period on intestinal microbiota. We found that ultra-early weaning impaired growth performance of piglets, of which worse body weight, average daily gain, feed intake, feed efficiency, and growth rate were observed in 14W group at all measured timepoints in comparison to those in 28W group (P<0.05). Moreover, higher contents of serum IgA (P=0.028), IgG (P=0.041), and IgM (P=0.047), as well as lower contents of serum albumin (P=0.002), albumin to globulin ratio (P=0.003), and total protein (P=0.004), were observed in 14W group in comparison to those in 28W group on day 28 of age, while not day 70 of age. High-throughput pyrosequencing of 16S rRNA indicated that the intestinal microbiota richness in 14W group was lower than that in 28W group (P<0.05), moreover, in comparison to 28W group at all sampling timepoints, fecal microbiota in 14W group showed more beneficial bacteria and fewer pathogenic bacteria (P<0.05). Therefore, we considered that ultra-early weaning had positive effects on immune status and fecal microbiota composition in piglets, but negatively affected growth performance and fecal microbiota abundance.